Simultaneous Transcatheter Pulmonary Balloon Valvuloplasty and Atrial Septal Defect Closure in Adult Patient - Deasy Eka Wardhani; Eka Prasetya Budi Mulia; Dita Aulia Rachmi (Universitas Airlangga, 2022)
Background: Percutaneous pulmonary balloon valvuloplasty (PBV) has become the first choice of management in patients with valvular pulmonary stenosis, while transcatheter closure in secundum atrial septal defect (ASD) is an alternative therapy besides surgical closure. The combination of PBV and transcatheter ASD closure is an action that is possible to do, but rarely done. Case Illustration: We present a case of 26-year-old woman with severe pulmonary stenosis and secundum ASD. Echocardiographic examination revealed the presence of severe pulmonary stenosis (mean gradient 99.19 mmHg) and defects in the intra atrial septum (with a size of 1.3 cm). Cardiac catheterization revealed right ventricular pressure of 160 mmHg. This patient then successfully corrected with both procedures ASD closure and PBV simultaneously. Discussion: These procedures have high feasibility, good safety, and shows good effectiveness. There were no complications during the procedures, and a satisfying immediate outcome was obtained. Conclusion: Pulmonary stenosis and atrial septal defects are rare forms of congenital heart disease. Transcatheter pulmonary balloon valvuloplasty and atrial septal defect closure performed simultaneously are promising alternatives, apart from surgical correction. Keywords: Atrial septal defect closure, Percutaneous pulmonary balloon valvuloplasty, Pulmonary stenosis